Experimental Research on the Thermal Performance of Composite PCM Hollow Block Walls and Validation of Phase Transition Heat Transfer Models. (26th January 2016) - Zhang, Yuan; Zhuang, Sunqi; Wang, Qian; He, Jiapeng
Abstract : A type of concrete hollow block with typical structure and a common phase change material (PCM) were adopted. The PCM was filled into the hollow blocks by which the multiform composite PCM hollow blocks were made. The temperature-changing hot chamber method was used to test the thermal performance of block walls. The enthalpy method and the effective heat capacity method were used to calculate the heat transfer process. The results of the two methods can both reach the reasonable agreement with the experimental data. The unsteady-state thermal performance of the PCM hollow block walls is markedly higher than that of the wall without PCM. Furthermore, if the temperature of the PCM in the wall does not exceed its phase transition temperature range, the PCM wall can reach high thermal performance.